Avaliação numérica da largura efetiva de pontes em seção caixão mista de aço e concreto com grau de interação total e parcial - Nicoletti, Renato Silva (Universidade Federal de São Carlos, 2021)
The present paper aims to numerically determine in the Abaqus® software, in a qualitative and quantitative way, the parameters that exert the greatest influence on the effective width of steel-concrete composite box girder bridges. These structures have advantages such as greater torsional rigidity, facilities in terms of construction and maintenance, durability and aesthetic factors. In the technical standards and in the literature, there is no specific recommendation for the calculation of the effective width in steel-concrete composite bridges with box girders and, as an alternative, the existing recommendations for I-girders are adopted. ”, The main ones being the American standard AASHTO (2017) and the European EN 1994-2-2 (2005) in addition to methods from the literature. In view of this range of procedures, there is a need for an investigation into the distribution of stresses at the interface between materials, because if the effective width is admitted incorrectly, costly or even unsafe solutions may result. For this purpose, the effective numerical width of 260 simply supported models of steel-concrete composite box girder bridges ridges of steel and concrete supported was determined, in which the study variables were the configuration of the cross section, the height of the concrete slab, the length of the span, the arrangement of elements in the cross section and the steel-concrete interaction degree. Based on the results found, expressions were proposed to calculate the effective width of steel-concrete composite box girder bridges, as well as coefficients, depending on the interaction degree, to adjust the effective width recommended by AASHTO (2017) and EN 1994-2-2 (2005) for steel-concrete composite bridges with I-girders.
Numerical assessment of effective width in steel-concrete composite box girder bridges with total and partial interaction
Keywords: Pontes mistas de aço e concreto; Largura efetiva; Seção caixão; Interação total e parcial; Análise numérica; Steel-concrete composite bridges; Effective width; Box girders; Total and partial interaction; Numerical analysis; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS